Alternative Crassulacean Acid Metabolism Modes Provide Environment-Specific Water-Saving Benefits in a Leaf Metabolic Model. Issue 12 (22nd October 2020) - Töpfer, Nadine; Braam, Thomas; Shameer, Sanu; Ratcliffe, R. George; Sweetlove, Lee J.
Abstract : Stoichiometric modeling of leaf metabolism reveals metabolic and morphological determinants for introducing Crassulacean acid metabolism and alternative water-saving flux modes into a C3 leaf in different environments. Abstract: Crassulacean acid metabolism (CAM) evolved in arid environments as a water-saving alternative to C3 photosynthesis. There is great interest in engineering more drought-resistant crops by introducing CAM into C3 plants. However, it is unknown whether full CAM or alternative water-saving modes would be more productive in the environments typically experienced by C3 crops. To study the effect of temperature and relative humidity on plant metabolism in the context of water saving, we coupled a time-resolved diel (based on a 24-h day-night cycle) model of leaf metabolism to an environment-dependent gas-exchange model. This combined model allowed us to study the emergence of CAM as a trade-off between leaf productivity and water saving. We show that vacuolar storage capacity in the leaf is a major determinant of the extent of CAM. Moreover, our model identified an alternative CAM cycle involving mitochondrial isocitrate dehydrogenase as a potential contributor to initial carbon fixation at night. Simulations across a range of environmental conditions show that the water-saving potential of CAM strongly depends on the daytime weather conditions and that the additional water-saving effect of carbon fixation by isocitrate dehydrogenase can reach 11% total water saving for the conditions tested.